Aktywność kobiet w wyborach na urząd prezydenta miasta Rzeszowa w latach 2002–2018 - Niewiadomska-Cudak, Małgorzata (Wydawnictwo Uniwersytetu Rzeszowskiego, 2020)
The article deals with the activity of women in the elections to the enforcement authority in Rzeszów over the period of 16 years, i.e. from the moment the act on the direct election of a commune head, town mayor and president came into force. An attempt was made to analyze the women's electoral participation in the candidacy for the position of mayor or president from the political science perspective. The choice of the place of this city is not without significance, as the feminization rate (the women’s involvement in local government authorities in cities with poviat status), indicates that Rzeszów came 62 out of 66 cities (Swianiewicz, Łukomska, 2020, s. 9). Examining the representation of female voters in five elections not only gauges the phenomenon of female gender participation, but also helps to understand the problem of under-representation of women among presidents at the city level with poviat rights. The article complements the discussions on the participation of women in local government authorities, but also fills a significant cognitive gap in research on the representation of women in local politics.
The activity of women in the elections for the office of the President of the city of Rzeszów (2002–2018)
Keywords: local elections; the president; women's representation; local government; executive body